Tata Ruang Masyarakat Pendukung Tradisi Megalitik: Kasus Masyarakat Baduy - Raden Cecep Eka Permana (Berkala Arkeologi, 1995)
The nature of archaeological data which is limited in quality and quantity has spurred us to strive to obtain, record and interpret these data. The farther the time span is from now, the more limited the data that reaches us. Data about prehistoric culture, for example, has very limited material, let alone interpret it. One of the efforts that can be done is to make an analogy to today's society that still carries out these prehistoric cultural traditions. This effort is often called an ethnographic or ethnoarcheological analogy. By looking at the practices that apply to the community, it is hoped that it can explain the meaning, function, and so on of the archaeological objects of the supporting community.